The talented Mr. Ripley - Minghella, Anthony; Damon, Matt; Paltrow, Gwyneth 1972-; Law, Jude; Highsmith, Patricia 1921- (Miramax International, 2000)
Tom Ripley is a calculating young man who believes its better to be a fake somebody than a real nobody. He's hired to go to Italy to bring back the playboy son of a millionaire and soon is plunged into a daring scheme of duplicity, lies and murder.